2007
DOI: 10.3386/w12850
|View full text |Cite
|
Sign up to set email alerts
|

The Overvaluation of Renminbi Undervaluation

Abstract: An earlier version of the paper was circulated under the title "Why the Renminbi Might Be Overvalued (But Probably Isn't)." We thank the discussant Barry Eichengreen, Michael Klein (whose suggestion inspired the title),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
122
2
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 129 publications
(135 citation statements)
references
References 16 publications
9
122
2
2
Order By: Relevance
“…2 As mentioned in the introduction, China is accused of maintaining the RMB rate below its equilibrium level to favor exports. Cheung et al (2007) conducted an empirical analysis that found little evidence of the RMB undervaluation. Eichengreen (2007) refuted that their findings could be interpreted as a rejection of the RMB undervaluation hypothesis because their empirical strategy (i.e.…”
Section: The Resultsmentioning
confidence: 99%
“…2 As mentioned in the introduction, China is accused of maintaining the RMB rate below its equilibrium level to favor exports. Cheung et al (2007) conducted an empirical analysis that found little evidence of the RMB undervaluation. Eichengreen (2007) refuted that their findings could be interpreted as a rejection of the RMB undervaluation hypothesis because their empirical strategy (i.e.…”
Section: The Resultsmentioning
confidence: 99%
“…To answer this question, we estimate exchange rate misalignment adjusting for the Balassa-Samuelson effect. Specifically, we regress the real exchange rate at PPP on real percapita GDP and calendar-year fixed effects, and the extent of misalignment is measured as the difference between the log of the real exchange rate at PPP and the log of the fitted value from the regression (as in Cheung et al, 2007;Frankel, 2006;Rodrik, 2007). The middle panel of Fig.…”
Section: Economic Characteristics Before and During Surgesmentioning
confidence: 99%
“…15 The empirical evidence for the HBS effect is mixed. While Chinn (2000), Bergin et al (2006), and Thomas and King (2008) find empirical support for the HBS effect, Lothian and Taylor (2008) and Cheung et al (2007) find weak evidence. I quantify the HBS effect by measuring the labor productivity of China relative to the United States.…”
Section: Harrod-balassa-samuelson (Hbs) Effectmentioning
confidence: 86%